Enhanced cell killing in lewis lung carcinoma and a human pancreatic-carcinoma xenograft by the combination of cytotoxic drugs and misonidazole. - Stephens, T. C. (Nature Publishing Group, 1981)
The "chemosensitizing" properties of the radiosensitizer misonidazole (MISO) were examined in 2 tumour systems, murine Lewis lung carcinoma and human pancreatic adenocarcinoma xenografted into immune-suppressed mice, using a soft-agar colony assay to measure tumour-cell survival. In mice bearing Lewis lung tumour, the administration of MISO simultaneously with melphalan, cyclophosphamide. CCNU, FU or vincristine gave substantial enhancement of cytotoxicity (DEFs from 1.5 to 3.5). However, no enhancement was seen with bleomycin, VP 16-213 or cis-Pt. The same level of enhancement of cyclophosphamide effect (DEF = 2.0) was seen with both cell survival and growth delay end-points effect (DEF = 2.0) was seen with both cell survival and growth delay end-points of tumour response. Enhancement was also seen in the human tumour xenograft with melphalan, cyclophosphamide and MeCCNU, using a cell survival assay, but cis-Pt was again not enhanced.